2020
DOI: 10.3390/plants9121763
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological, Yield and Quality Traits and Interrelationship with Yield Stability in Quinoa (Chenopodium quinoa Willd.) Genotypes under Saline Marginal Environment

Abstract: Quinoa (Chenopodium quinoa Willd.) is a halophytic crop that shows resistance to multiple abiotic stresses, including salinity. In this study we investigated the salinity tolerance mechanisms of six contrasting quinoa cultivars belonging to the coastal region of Chile using agro-physiological parameters (plant height (PH), number of branches/plant (BN), number of panicles/plant (PN), panicle length (PL), biochemical traits (leaf C%, leaf N%, grain protein contents); harvest index and yield (seed yield and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
6
24
0
Order By: Relevance
“…Panicle lengths between 22 and 40 cm have been reported (Lopez et al, 2012) and, in this study, we found panicles between 12 and 45.6 cm in length. Studies have shown a strong correlation between the panicle diameter and yield (Hussain et al, 2020). Panicle diameters in this study ranged from 7.5 to 38.2 cm, which corroborates Morillo et al (2020) in the study on the intrapopulation phenotypic variation in the material cultivated of Boyacá, Piartal, where a high diversity was found at the interindividual level, mainly in length, diameter, and color of the panicle.…”
Section: Resultssupporting
confidence: 91%
“…Panicle lengths between 22 and 40 cm have been reported (Lopez et al, 2012) and, in this study, we found panicles between 12 and 45.6 cm in length. Studies have shown a strong correlation between the panicle diameter and yield (Hussain et al, 2020). Panicle diameters in this study ranged from 7.5 to 38.2 cm, which corroborates Morillo et al (2020) in the study on the intrapopulation phenotypic variation in the material cultivated of Boyacá, Piartal, where a high diversity was found at the interindividual level, mainly in length, diameter, and color of the panicle.…”
Section: Resultssupporting
confidence: 91%
“…64 Allelochemicals exert their phytotoxic effects through different pathways, and the biological activity on the target weeds also varies from one weed to another. 5,43,65 Allelochemicals can be considered an important part of ecological weed management, but it is necessary to understand the class of allelochemicals and their possible mechanisms of action. 5 In the present study, we quantified the polyphenols (phenolic acids, flavonoids) and hydroxamic acids and their subsequent distribution in plant tissues (roots and shoots) as well as from the root rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show the first phenotyping assessment carried out on a comprehensive set of quinoa accessions from the USDA germplasm collection accounting for yield and its components. This collection was the basis of several adaptations and breeding programs internationally and, as such, made a highly significant contribution to the global expansion of this crop [ 17 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. According to our results, the environment contributed to phenotypic variation in most traits ( Table 1 ); however, their magnitude was relatively low compared with contributions of G and G × E effects.…”
Section: Discussionmentioning
confidence: 99%